EVALUASI PERJALANAN REFORMASI BIROKRASI DI INDONESIA PERIODE 2020–2025 - Zaenal Abidin AS (Jurnal Academia Praja, 2026)
Bureaucratic reform constitutes a national strategic agenda aimed at establishing governance that is effective, efficient, transparent, and oriented toward high-quality public service. This article evaluates the trajectory of bureaucratic reform in Indonesia during the 2020–2025 period by focusing on policy directions, major achievements, implementation challenges, and their implications for public service quality and the performance of civil servants. This study adopts a qualitative approach through a literature review and policy analysis of regulatory frameworks, official evaluation reports issued by Kementerian Pendayagunaan Aparatur Negara dan Reformasi Birokrasi, national development planning documents published by Kementerian PPN/Bappenas, and relevant academic publications. The analysis is guided by an integrated theoretical framework drawing on New Public Management, New Public Service, Good Governance, and Digital Government perspectives to assess performance orientation, service orientation, governance quality, and the extent of digital transformation. The findings indicate that the 2020–2025 period was characterized by an acceleration of bureaucratic reform, particularly in organizational streamlining, the strengthening of performance accountability systems, and the expansion of digital-based public services. These reforms have contributed to greater administrative efficiency and improved accessibility of public services. Nevertheless, significant challenges remain, notably limited interoperability among digital government systems, uneven human resource capacity across regions, and inconsistent policy implementation at the levels of ministries, agencies, and local governments. This study concludes that the sustainability of future bureaucratic reform requires stronger system integration, continuous capacity building of civil servants, and more consistent cross-sectoral and multilevel policy coordination.